2011
DOI: 10.1002/smll.201002350
|View full text |Cite
|
Sign up to set email alerts
|

Thin‐Film‐Based Nanoarchitectures for Soft Matter: Controlled Assemblies into Two‐Dimensional Worlds

Abstract: Controlling the organization of molecular building blocks at the nanometer level is of utmost importance, not only from the viewpoint of scientific curiosity, but also for the development of next-generation organic devices with electrical, optical, chemical, or biological functions. Self-assembly offers great potential for the manufacture of nanoarchitectures (nanostructures and nanopatterns) over large areas by using low-energy and inexpensive spontaneous processes. However, self-assembled structures in 3D me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
114
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(116 citation statements)
references
References 318 publications
(307 reference statements)
1
114
0
1
Order By: Relevance
“…12,13 In particular, engineering processes aimed at scaleup of ultrathin film preparation has been investigated from the point-ofview of future practical applications. For example, Yan et al 14 reported epitaxial formation of bilayer Bernal graphene on copper foil through chemical vapor deposition process.…”
Section: How To Structure Functional Layersmentioning
confidence: 99%
“…12,13 In particular, engineering processes aimed at scaleup of ultrathin film preparation has been investigated from the point-ofview of future practical applications. For example, Yan et al 14 reported epitaxial formation of bilayer Bernal graphene on copper foil through chemical vapor deposition process.…”
Section: How To Structure Functional Layersmentioning
confidence: 99%
“…Self-assembly as a tool to form long-range interconnected 1D-or 2D-nanostructures with tuneable optical, electrical and magnetic properties may represent a possible solution towards the mass production of molecular circuits. In such a case, the fabrication of nanostructures would completely rely on spontaneous bottom-up processes depending on different factors: geometry and chemical nature of the building blocks, and their intermolecular forces (that is, Coulombic, van der Waals, dipolar and p-p) [9][10][11][12][13][14][15][16] . The chemical fine tuning of the selected building blocks is an interesting approach, which may give rise to selective formation of interconnected nanoarchitectures after selfassembly.…”
mentioning
confidence: 99%
“…The assembly of these components can be directed by a variety of interparticle forces, 152 which are commonly used to create molecular monolayers on surfaces, which is extremely useful for thin film applications, 153 and ordered arrays of nanoparticles. 154 This has proven to be an extremely useful tool for nanofabrication, with an extensive body of research investigating the various methods and applications of self-assembly.…”
Section: Self-assemblymentioning
confidence: 99%
“…Selfassembly is therefore not available as a standalone fabrication method that can build completely arbitrary assemblies, but it does allow for existing surfaces and objects to be functionalised to perform other useful tasks, 153,158,159,160 including large-scale growth of features like carbon nanotubes for circuits. Patterning areas of a surface for self-assembly, although limited to the resolution of the preceding lithography steps, can even direct the very precise manipulation of nanoparticles individually.…”
Section: Self-assemblymentioning
confidence: 99%